TECHNO-ECONOMIC EVALUATION FOR THE DEVELOPMENT OF LOW RESISTIVITY AND LOW CONTRAST RESERVOIR WITH HYDRAULICALLY FRACTURED WELL AND WATER INJECTION - Kevin Wibowo, Vinsensius
X field is an example of a low resistivity and low contrast (LRLC) reservoir found in South Sumatra, with initial oil content in the one pattern of reservoir estimated at 3.48 MMSTB. This field has reserves that can be produced up to 30% but it has relatively low permeability value. The processes that can be used to stimulate the wells in low permeability reservoir are hydraulic fracturing and water injection. This study aims to analyze the application of hydraulic fracturing and water injection in the X field and review its feasibility using simple economic analysis. By using the results of the model initialization, reservoir simulation using the CMG Builder program is carried out through six base cases representing the wide heterogeneity of reservoir. From this simulation, the original oil in place, recovery factor, cumulative production, and production rate values are obtained for each base case. At this stage, the six base cases are given field development in the form of hydraulic fracturing and water injection. Each base case has seventeen development cases. From this simulation, the recovery factor, cumulative production, and production rate values are obtained for each development case. From the result of economic analysis shows that the most appropriate development method for the LRLC zone on the X field is hydraulic fracturing. The application of water injection to hydraulic fractured wells in the LRLC zone only provides increased production but does not provide greater economic benefits.